Building The Independence of The Defense Industry Through the Subcontractor System (Study of Indonesian-British Cooperation in The Development of The AH140 Frigate) - Rakha Al-Hakim Gobel; Jupriyanto , Jupriyanto; George Royke Deksino; M. Taufiq Ramadhan; Vicky A Nugroho; Wulan Nurfitriani; Surahman, Surahman; Mahardhani Wahyu A (CV. AFDIFAL MAJU BERKAH, 2023)
More complex forms of threats, not only in the form of military threats but non-military threats, are increasingly sophisticated due to the presence of increasingly new technologies and targets of cybercrime which also target various business sectors such as construction companies because of the great value in their cooperation. In 2021, Indonesia will cooperate with the United Kingdom to develop the AH140 frigate through the Merah Putih Frigate, outlined in a Joint Operation Agreement. What is interesting is Babcock Marine's concern as the party cooperating with PT. PAL in subcontracting this project. In order to answer these concerns, a study is needed regarding the subcontractor system in Indonesia, which can be used as a contribution to building the independence of the Indonesian defense industry. The research method used in this study is a descriptive approach, a qualitative research type using library research methodology through credible books, journals, and news to be used for research studies. It can be concluded that the subcontractor system in defense industry projects has contributed to the government's efforts to build defense industry independence. However, subcontractors need more support in developing their capabilities